Studi Deskriptif Manajemen Pengelolaan Zakat Pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Langkat - Agustina Ning Pratiwi; Mutiara Khairani; Muhammad Nur iqbal (CV. ITTC INDONESIA, 2026)
This study aims to describe the zakat management at the National Zakat Agency (BAZNAS) in Langkat Regency, including the zakat collection and distribution process, the programs implemented, and the efforts and obstacles encountered in zakat management. This study employed a qualitative field research method. Data were obtained through interviews with BAZNAS Langkat Regency administrators and supported by secondary data in the form of books, journals, and regulations related to zakat management. The results indicate that BAZNAS Langkat Regency has implemented zakat management through a structured collection, management, and distribution process. Furthermore, BAZNAS has various zakat distribution programs covering health, education, economics, humanitarianism, and religion. However, its implementation still faces several obstacles, such as low community participation, limited human resources, and suboptimal use of technology. Therefore, BAZNAS continues to strive to improve the quality of zakat management through the establishment of Zakat Collection Units (UPZ), outreach programs, and improving the competence of zakat collectors.